BALB/c myeloma retroviruses have mink cell focus-inducing activity. - Spriggs, D R (1980)
We have determined the in vitro host range of the cloned MO-21 and FL-1 murine myeloma retroviruses grown in SC-1 cells that were originally isolated from cloned MOPC-21 and FLOPC-1 BALB/c plasmacytoma cell lines. These viruses are able to replicate in murine (BALB/3T3, NIH/3T3) as well as numerous heterologous cell lines. These myeloma retroviruses also exhibit mink cell focus-inducing activity. MO-21 and FL-1 shared interference patterns with each other, but their replication was not interfered with by ecotropic, xenotropic, or amphotropic viruses. The lack of cross-interference with ecotropic or xenotropic viruses distinguishes these isolates from other mink cell focus-inducing viruses.